Pengembangan Sistem Kasir Berbasis Web dengan Model Agile pada CV. Permata Garden - Tampubulon, Jefi Eliel Tigor; Adhityansyah, Caesar; Razik, Muhammad; Haryono, Wasis (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
CV. Permata Garden is a shop that focuses on selling tools for ornamental flowers. However, in its daily activities, it still applies a manual transaction system that has a negative impact on efficiency and accounting. To solve this problem, a web-based cashier system was developed with an Agile approach. This system is designed to automatically record every transaction, facilitate monitoring of transaction history, manage inventory, and present sales reports directly. This study adopts observation, interview, and library observation methods for data collection. The results of this work practice are in the form of a cashier web application that can be used by admins, employees, and management to support operational activities in a more efficient and structured way. It is estimated that the implementation of this system will be able to increase productivity, reduce errors in recording, and be the first step towards digitalizing the business at CV. Taman Permata.